Distribution of White-to-White Corneal Diameter and Anterior Chamber Depth in Chinese Myopic Patients - Xu, Guihua; Wu, Guanrong; Du, Zijing; Zhu, Shanqing; Guo, Yunxiang; Yu, Honghua; Hu, Yijun (Frontiers in Medicine, 2021)
Purpose: To investigate the distribution of white-to-white (WTW) corneal diameter and anterior chamber depth (ACD) in Chinese myopia patients. Methods: This was a cross-sectional observational study conducted at five ophthalmic centers. Anterior segment biometry was performed in 7,893 eyes of the 7,893 myopic patients using Pentacam, and the WTW and ACD were recorded. The distribution patterns of WTW and ACD were evaluated and the correlation between WTW and ACD was analyzed statistically. Results: There were 4416 (55.95%) males and 3477 (44.05%) females. The age of the study population was 25.14 ± 5.41 years. Distribution of WTW was slightly positively skewed (Skewness = 0.0076, Kurtosis = 0.3944, KS P = 0.020) with a mean of 11.65 ± 0.38 mm and a 95% normal range of 10.91–12.39 mm. A significant difference in WTW was found among different myopia groups (P < 0.001). The ACD was normally distributed (Skewness = 0.899, Kurtosis = 0.027, KS P = 0.086). The mean ACD was 3.25 ± 0.26 mm and the 95% normal range of was 2.74–3.75 mm. A significant difference in ACD was also found among different myopia groups (P = 0.030). There was a significant correlation between WTW and ACD (r = 0.460, P < 0.001). Conclusions: In our study, 95% of the Chinese myopic patients had a WTW within 10.91–12.39 mm and an ACD within 2.74–3.75 mm. ACD and WTW were significantly different among different myopia, gender and age groups. WTW was positively correlated with ACD.